PERAN BUDAYA KAPIRI KAME SUKU KAMORO (MIMIKA WEE) DALAM MENGUPAYAKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Tastutik Romawandhoni (Journal of Education Papua Baru, 2022)
Abstract:Â This writing aims to produce additional knowledge and understanding of cultural traditions or habits in society related to the motivation of elementary school students in grade VI, a tradition, custom, or culture that exists in the Kamoro people, namely Kapiri Kame (going somewhere to look for food by taking their children along for an indefinite period of time and making a simple building for a stopover while their activities have not been completed). Most people view the Kapiri Kame culture as very influential on students' learning motivation where there is a public view that students are disadvantaged by this cultural tradition which is still carried out mostly by the Kamoro tribe in the Mimika district. Stakeholders need special attention. In this case, the Education Office and the Regional Government must pay attention and find good solutions so that this nationâ€™s next generation can learn continuously. Community leaders need to explain the importance of formal learning for their children so they can compete in the future and this should be done regularly and continuously.Keywords: Kapiri Kame Tradition, motivation to learn